The Effect of Laser Irradiation to Surfaces of Computer-Aided Design/Computer-Aided Fabrication Resin Blocks Coated with a Silane Coupling Agent on Bond Strength between the Resin Blocks and Composite Resin - Hiroshi Ohno; Masaya Suzuki; Koichi Shinkai (MDPI AG, 2023)
The aim of this study was to investigate the effect of laser irradiation to computer-aided design/computer-aided fabrication (CAD/CAM) resin blocks coated with a silane coupling agent on the bond strength between resin blocks and composite resin. The CAD/CAM resin blocks used in this study were Cerasmart 300 (GC) and Vita Enamic (Vita); they were cut into plates and then subjected to a series of treatments. After processing with a silane coupling agent, treatment with a semiconductor laser was performed at 3.0, 5.0, and 7.0 W, followed by bonding procedures. The control group included those exposed to silane and bonded without laser application. After bonding, a mold with a simulated cavity was formed on the specimen and filled with flowable composite resin, and they were stored for 24 h or stressed by thermal cycling for subsequent testing that assessed the shear bond strength (n = 10). The results revealed that the bond strength was significantly enhanced by laser irradiation after applying a silane coupling agent (p < 0.03), whereas significant increase was not detected between the materials (p > 0.05). Particularly, 7 W laser irradiation had a significant increase on the bond strength between the composite resin and Cerasmart block after thermal cycling (p = 0.009). The SBS of the composite resin to CAD/CAM resin blocks was significantly enhanced by laser irradiation after silane coupling agent application.